The Role of Indonesian Women in Defending the Country Efforts in Facing the Covid-19 Pandemic: Peran Perempuan Indonesia dalam Upaya Bela Negara Menghadapi Pandemi Covid-19 - Tatara, Beny Abukhaer; Retnaningsih, Wahyu Sekti (Journal of Multidisciplinary Science, 2023)
The Covid-19 pandemic is one of the threats to defending the life of the Indonesian nation and state. In facing all forms of disturbing threats, the Indonesian nation adheres to a universal people's defense and security system, so efforts to defend the nation to defend the nation from various existing threats are the obligation and responsibility of the entire Indonesian nation including women. This study aims to analyze the role of women in efforts to defend the country against the pandemic. This research uses qualitative methods with a literature study approach. The results of the study show that women's involvement in efforts to defend the state in Indonesia has existed since colonialism and the war against colonialism. The role of women in efforts to defend the country against the Covid-19 pandemic is realized through the basic values ​​of defending the country, namely: love for the motherland, awareness of nation and state, willingness to sacrifice for the nation and state, and possessing the initial ability to defend the country.